Evaluation of bio-control agents and new fungicides to control Pythium damping off in nursery of solanaceous vegetable crops - Tripathi, AN; Singh, Rajesh Kumar; Tiwari, SK (Vegetable Science, 2022)
Nursery of solanaceous vegetable crops severely infectedby damping - off. Commercial cultivation of solanaceousvegetables are depends on healthy and disease free seedlingsunder nursery condition in fields. Seed treatments are mostcost effective and commonly used delivery system for bioagentsand fungicides. Nine modules comprises three talcbased fungal [Trichoderma viride- 1 (IIVR–BATF-39-1), T.viride-2 (IIVR-BATF-43-1), Trichoderma harzianum -Kalyanpur)], two bacterial (Bacillus subtilis (IIVR-BS2,Pseudomonas fluorescens -Kalyanpur) formulations andfour fungicides (carbendazim 12% + mancozeb 63% WP,pencycuron 250 SC, fosetyl-Al 80% WP, fenamidone 10% +mancozeb 50% (WP) were evaluated under nursery oftomato, brinjal and chilli in kharif season during 2016-2018.Among tested bio-formulations of bio-agents Bacillussubtilis (IIVR-BS2 ) was found effective for highestgermination percentage in tomato (84.77) and brinjal (66.81)and lowest incidence of damping off 15.22% and 33.18%,repectively whereas cost benefit ratio (CBR) 1: 79.98 (tomatovar. Kashi Aman) and 1: 36.69 (brinjal var Kashi Taru) wererecorded. However, among all tested modules, a fungicidecarbendazim 12% WP + mancozeb 63% WP was foundmost effective in chilli for highest germination percentage(86.58), vigour index (479.52) and lowest incidence ofdamping off (13.30) with cost benefit ratio (CBR) 1: 90.79.Hence, use of bio-agent Bacillus subtilis (IIVR-BS2)3.92×1011 cfu/g in tomato and brinjal; however, combiproductof carbendazim (12%) and mancozeb (63%) in chilli may berecommended for management of damping off in nursery.